Structural elucidation of propargylated products of 3-substituted-1,2,4-triazole-5-thiols by NMR techniques - Chaudhary, Preeti M.; Chavan, Sayalee R.; Kavitha, M.; Maybhate, Shailaja P.; Deshpande, Sunita R.; Likhite, Anjali P.; Rajamohanan, P. R. (Magnetic Resonance in Chemistry, 2008)
Propargylation of 3-substituted-1,2,4-triazole-5-thiols, which predominantly exist as their thione tautomers, was carried out with the view to synthesize different heterocycles and study their biological activity. Three different products namely, a mono S-propargyl and two S,N-dipropargyl regioisomers, arising from N1/N2 substitution, were isolated and characterized. Unambiguous structural elucidation of the regioisomers of S,N-dipropargyl derivatives was achieved by means of (13)C-(1)H HMBC technique. The proportion of the regioisomers was found to vary with the substituent on the 1,2,4-triazole thiols. No product corresponding to N4 substitution was isolated from any of the reactions carried out. Copyright (C) 2008 John Wiley & Sons, Ltd.
Keywords: (1)H NMR; (13)C NMR; (15)N NMR; 1; 2; 4-triazoles; HMBC; NMR; Regioisomers